A survey of the macroepiphytes of Mt. Balugo, Tacloban City - Amoylen, Agnetha Jane Mari; Cadavis, Maricel Pesao; Monge, Glenn Carrozo; Soledad, Donna Ann Santos (Tacloban City Division of Natural Sciences and Mathematics, University of the Philippines Visayas Tacloban College, 2000)
A survey of the macroepiphytes in Mt. Balugo, Tacloban City was conducted from January to February 2000. From the three different levels of the mountain, peak (80-120 m ASL), middle (60-80 m ASL), and bottom (20-60 m ASL), A total of 31 macroepiphytes were collected and classified except for 2 species remained unidentified. The middle part of the mountain (site B) had the highest number of species reaching a total of 26 and is the most diverse as indicated by the species richness index (10.85). It is followed by the bottom (site A) with a total of 13 species and the peak (site C) having 3 species only. Similarity index value between sites A and B is 0.41, and 0.21 between sites B and C suggesting an uneven distribution of the different epiphyte species in Mt. Balugo.
The species Rhaphidophora spp. is the most abundant species but is not widely distributed in Mt. Balugo.
Undergraduate thesis (Bachelor of Science in Biology) -- University of the Philippines, Tacloban.